2003
DOI: 10.2519/jospt.2003.33.10.594
|View full text |Cite
|
Sign up to set email alerts
|

The Female Athlete Triad: An Emerging Role for Physical Therapy

Abstract: Over the last thirty years, participation by girls and women in organized athletics has increased dramatically. This presents unique challenges in the area of sports medicine, orthopaedics, and pediatrics. While the benefits of participation in sports and exercise vastly outweigh the risks of permanent injury, an evolving concern is the number of stress fractures in active women. The female athlete triad (''triad'') describes the coexistence of 3 distinct medical conditions that may occur in athletic girls and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 56 publications
0
17
0
5
Order By: Relevance
“…Current amenorrhoeic research relates to athletes and the triad of amenorrhoea/oligomenorrhoea, disordered eating and decreased bone density (Papanek, 2003). More recently, energy balance has been added to this triad (Andrico et al, 2002;Harber, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Current amenorrhoeic research relates to athletes and the triad of amenorrhoea/oligomenorrhoea, disordered eating and decreased bone density (Papanek, 2003). More recently, energy balance has been added to this triad (Andrico et al, 2002;Harber, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that the female athlete triad syndrome includes eating disorders/disordered eating behavior, amenorrhea/oligomenorrhea, and decreased bone mineral density (osteoporosis/osteopenia) [6] leads the medical and training staff to pay strong attention to the adolescent female health. The major focus when caring for the adolescent athlete should be the diagnosis of the triad syndrome [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Although our patient was at high risk to develop generalised osteopenia due to low dietary energy (eating disorder, anorexia and weight loss), administration of non-steroidal anti-inflammatory medications that inhibit COX223 and prolonged high dose of antiepileptic gabapentin, suppression of oestrogen and decrease of BMD (ovariectomy, hysterectomy in the past and chronic negative energy balance)24 repeat of DEXA scan during the follow-ups showed that low BMD remained localised to the pubic region.…”
Section: Discussionmentioning
confidence: 71%